2022
DOI: 10.3390/su15010449
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Stock Assessment in Silvopastoral Systems along an Elevational Gradient: A Study from Cattle Producers in the Sumaco Biosphere Reserve, Ecuadorian Amazon

Abstract: Silvopastoral system (SPS) has been considered as a sustainable management system contribute to greenhouse gas (GHG) reduction, among other benefits compared with open pasture. However, little research has been conducted on the soil and tree biomass carbon stored in traditional pasture with dispersed trees (PWT) compared with pasture in monoculture (PM). The present study was conducted in the Ecuadorian Amazon Region (EAR), along an elevational gradient from 400 to 2000 masl., within the buffer and transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
0
15
1
Order By: Relevance
“…The TAGC in CMC (Table 6) is higher than that reported in cocoa monocultures in Nicaragua [9]. But it is still very low compared to what was found in FAFS and TAFS, which allows us to infer that the storage of AGC in any type of AFS depends on the management, crop age, diversity, and density of tree species [2,20,34], unlike a monoculture that is limited to certain species. This means that the greater the diversity of species, the greater the carbon store [9,52].…”
Section: Stored Biomass Carbonmentioning
confidence: 72%
See 2 more Smart Citations
“…The TAGC in CMC (Table 6) is higher than that reported in cocoa monocultures in Nicaragua [9]. But it is still very low compared to what was found in FAFS and TAFS, which allows us to infer that the storage of AGC in any type of AFS depends on the management, crop age, diversity, and density of tree species [2,20,34], unlike a monoculture that is limited to certain species. This means that the greater the diversity of species, the greater the carbon store [9,52].…”
Section: Stored Biomass Carbonmentioning
confidence: 72%
“…This means that the greater the diversity of species, the greater the carbon store [9,52]. Furthermore, several studies affirm that the transition from monocultures to AFSs has a great potential to store carbon, which improves with the age and density of tree species [34,52], such as silvopastoral systems (SPSs) in the arid region of Colombia with 7.15 Mg C ha −1 [1] and other studies in Colombian territory (31 Mg C ha −1 ) [56]. In this context, it is confirmed that SPSs and AFSs are important management and improvement alternatives to counteract the expansion of the agricultural frontier and therefore minimize GHG emissions that lead to global warming.…”
Section: Stored Biomass Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in relation to the current year (2022), we observed a total of three articles. Among these articles, the most recent paper was published by Torres et al [105]; in this study, the researchers evaluated carbon stocks in silvopastoral systems in the Ecuadorian Amazon. Among the main findings reported in this study, the authors indicated the high potential of traditional grazing systems with dispersed trees for carbon sequestration in the Ecuadorian Amazon.…”
Section: The 10 Most Frequently Cited Documentsmentioning
confidence: 99%
“…Tree diversity is a key element in ecological resilience and the provision of multiple ecosystem services in traditional silvopastoral systems [1][2][3]. These systems, which integrate dispersed trees in pastures, are being recognized for their environmental [4][5][6] and economic benefits [7][8][9], highlighting the importance of tree diversity, which motivates an intense analysis along the Andean-Amazonian altitudinal gradient [7,10].…”
Section: Introductionmentioning
confidence: 99%